To know a word? an evaluation of the vocabulary acquisition tasks in selected web resources - Chin, Connie Swee Lan (Kota Samarahan : Universiti Malaysia Sarawak, 2007., 2007)
This is a research on vocabulary-related tasks in the web resources provided by the Malaysian Ministry of Education for the teaching of English for Science and Technology (EST) for students at the fifth form (17 years old). The research adopted the theory-based criteria approach derived from understandings of language learning processes (Kiely & Rea-Dickins, 2005). The data were collected from 30 English teachers through an evaluation checklist, followed by interviews. The findings revealed that the vocabulary component in the web resource may not be a feasible resource for teaching vocabulary as the four elements of language learning potential in the materials are not satisfactorily addressed. This resource evaluation outcome suggest that the materials are not exploited enough for the purpose of promoting language learning, and as a consequence, the acquisition of vocabulary may not be developed sufficiently. In relation to reading comprehension, the findings implied that the design of the web material needs to be improved in order to effectively bring about positive effects on learners’ reading comprehension. In relation to vocabulary development strategies, more variety can help to promote better vocabulary learning. The resources, however, have good web elements to be considered an effective web resource. The findings suggest that the design of the tasks for developing vocabulary acquisition should incorporate aspects of lexical sets, collocations, and teaching vocabulary through reading (Breen, 1983; Channell, 1981; Gairns & Redman, 1986; McKeown et al., 1985; Ooi & Lee 1996; Rivers, 1983).